We Are on the Verge of Breakthrough Cures for Type 1 Diabetes, but Who Are the 2 Million Americans Who Have It? - Rebecca Smith; Samara Eisenberg; Aaron Turner-Phifer; Jacqueline LeGrand; Sarah Pincus; Yousra Omer; Fei Wang; Bruce Pyenson (Journal of Health Economics and Outcomes Research)
# Background Two million Americans have type 1 diabetes (T1DM). Innovative treatments have standardized insulin delivery and improved outcomes for patients, but patients’ access to such technologies depends on social determinants of health, including insurance coverage, proper diagnosis, and appropriate patient supports. Prior estimates of US prevalence, incidence, and patient characteristics have relied on data from select regions and younger ages and miss important determinants.